2011
DOI: 10.1007/s00423-011-0817-4
|View full text |Cite
|
Sign up to set email alerts
|

Single incision laparoscopic cholecystectomy (SILC) versus laparoscopic cholecystectomy (LC)—a matched pair analysis

Abstract: SILC is associated with longer operating time, but equals LC with respect to safety, postoperative pain, use of analgesics, length of stay, return to work, rate of incisional hernia, and cosmetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
56
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 21 publications
7
56
1
3
Order By: Relevance
“…Few studies and meta-analysis had shown similar results as our study, and some studies had shown similar operative time in SILC. 12,14,16 Postoperative complications and mean hospital stay were similar in both groups. There was no incidence of bile duct injury and port-site hernia in both groups.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Few studies and meta-analysis had shown similar results as our study, and some studies had shown similar operative time in SILC. 12,14,16 Postoperative complications and mean hospital stay were similar in both groups. There was no incidence of bile duct injury and port-site hernia in both groups.…”
mentioning
confidence: 76%
“…Previous studies showed safety and feasibility of SILC with no significant intraoperative complications. [12][13][14] Few studies showed increased rate of intraoperative complications in SILC, but these are statistically insignificant. 15 Operative difficulty, such as compromised vision, insufficient retraction, difficult gallbladder extraction, and difficult instrumentation was noticed significantly higher in SILC.…”
Section: Discussionmentioning
confidence: 99%
“…An inference that agrees with almost all reported studies. [11][12][13][14] This is partly a reflection of the increased operating time during the initial learning curve and the clashing and restricted mobility of the instruments at the very narrow umbilical fulcrum and careful closure of the umbilical port. 15 Although others have reported equal times for SILC and SLC after the learning curve is over.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion rates reported vary from 9.3% to 14.9%. 14,16 Status of postoperative pain still remains unclear with varying reports in the literature of SILC resulting in less pain more pain or no difference as compared with SLC. Our figures suggest that though SILC has lower pain scores, there is no significant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there have been no severe complications, such as injury to the bile duct or conversion to laparoscopy or open surgery, 11,12 although one case of postoperative hemorrhage associated with SIRC has been reported. 13 Additionally, some authors have investigated cosmetic outcome and postoperative pain in comparative studies, 14,15 with less pain and better cosmetic outcomes occurring in SILC. 16,17 The results of the present study also showed good outcomes without any conversions or complications, even when no additional port was used during the procedure.…”
mentioning
confidence: 99%